Gravimetric quantitative validation of botanic impurities in feed. (31st August 2020) - Marchis, Daniela; Amato, Giuseppina; Giovannini, Tiziana; Khadjavi, Amina; Morello, Sara; Gili, Marilena; Pinotti, Luciano; Vrhovnik, Igor Ujčič
Abstract: Background: Harmful botanical impurities may contaminate feed and feed materials and be a potential danger to animal or human health, or to the environment. The aim of this study was to establish rapid and sensitive methods that can be used in routine official controls to determine botanical impurities such as Datura stramonium, Ricinus communis, Crotaliaria spp., and Ambrosia spp. in animal feed and raw materials. Claviceps sclerotia were also detected in cereals, due to the similarities of the targets and the analytical procedure. Regulation (EU) 625/2017, which replaces Reg. 2004/882/EC, states that EU member states should conduct official controls in assessed and accredited laboratories and that the analytical methods must be validated before use by considering parameters such as specificity, precision, recovery, and measurement uncertainly. Results and Conclusion: The results demonstrate that all of the methods tested are suitable for the official quantitative analyses required by EU official legislation. © 2020 Society of Chemical Industry